Ubezpieczenia obowiązkowe w rolnictwie - Łozowski, Mieczysław (The Obligatory Insurance in Agriculture, 2005)
Country and agriculture are the spheres of communal and economical life, which in the better part of capitalistic states fall under the sphere of state intervention and are a part of the state politic and protection. Agriculture is peculiarly open to the ruining effect of unfavourable events, which, with their extent, cause natural disasters. The paper describes research of growing of obligatory agricultural insurances after year 1997 and shows a view of their progress.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 45-49